Correction: Balaphas et al. Cell Therapy for Anal Sphincter Incontinence: Where Do We Stand? Cells 2021, 10, 2086 - Alexandre Balaphas; Jeremy Meyer; Raphael P. H. Meier; Emilie Liot; Nicolas C. Buchs; Bruno Roche; Christian Toso; Leo H. Bühler; Carmen Gonelle-Gispert; Frédéric Ris (Cells, 2023)
The authors would like to add a new reference to the section “3 [...]